Design and evaluation of a blended basketball training program using the ADDIE model - Jun Sun; Nipaporn Khamcharoen (PLoS ONE, 2025)
This study aimed to develop and evaluate a blended learning basketball training program for university students based on the ADDIE instructional design model. A quasi-experimental one-group pre-test–post-test design was conducted with 30 first-year undergraduates in Wuhu, China. Over five days (30 hours), participants engaged in online theoretical learning and offline practical sessions covering five basketball skill areas, followed by a satisfaction survey. All measured skills improved significantly (p < .001), with large effect sizes in dribbling (d = 2.14) and passing (d = 3.34), while improvements in shooting and three-step layups were relatively smaller but still significant. Mean satisfaction was 4.07/5, with high ratings for instructional support and learning resources. These findings support the effectiveness of the ADDIE-based blended learning model in enhancing basketball skills and student engagement. This structured approach offers practical value for improving skill acquisition in sports education.